Cervical Carcinoma in Early Pregnancy – Successful Birth by Caesarean Section Followed by Radical Hysterectomy - Schreiber, K.; Rothe, S.; Untch, M. (Geburtshilfe und Frauenheilkunde, 2014)
A cervical carcinoma was diagnosed in a 32-year-old patient in the 17th week of her pregnancy. The histological confirmation revealed a well-differentiated squamous cell carcinoma. It was a clinical stage Ib1 tumour, without enlarged lymph nodes according to the image. After a staging MRI, intensive education of the patient and case discussion at the interdisciplinary tumour board as well as consultation with the neonatologist, it was agreed to prolong the pregnancy under close monitoring. The carcinoma was confined to the cervix in the further course of the pregnancy. The elective delivery was planned after 32 weeks of gestation. The primary Caesarean section followed by radical hysterectomy Piver II were carried out without complications. After regular postoperative progression of the mother, brachytherapy was performed at the appropriate time. The premature newborn was under neonatal care and exhibited good postnatal adaptation. Mother and child were discharged in good health.
Keywords: cervical carcinoma; pregnancy; radical hysterectomy; Caesarean section